Transcriptomics Analysis Reveals Shared Pathways in Peripheral Blood Mononuclear Cells and Brain Tissues of Patients With Schizophrenia - Song, Xuemian; Liu, Yiyun; Pu, Juncai; Gui, Siwen; Zhong, Xiaogang; Chen, Xiaopeng; Chen, Weiyi; Chen, Xiang; Chen, Yue; Wang, Haiyang; Cheng, Ke; Zhao, Libo; et al. (Frontiers in Psychiatry, 2021)
Background: Schizophrenia is a serious mental disorder with complicated biological mechanisms. Few studies tried to explored the transcriptional features which shared in brain tissue and peripheral blood. In the present study, we aimed to explore the biological pathways with similar expression patterns in both peripheral blood mononuclear cells (PBMCs) and brain tissues. Methods: The present study used transcriptomics technology to detect mRNA expression of PBMCs of 10 drug-naïve patients with schizophrenia and 20 healthy controls. The transcriptome datasets of brain tissue of patients with schizophrenia downloaded from public databases were also analyzed in our study. The biological pathways with similar expression patterns in the PBMCs and brain tissues were uncovered by differential expression analysis, weighted gene co-expression network analysis (WGCNA), and pathway analysis. Finally, the expression levels of differential expressed genes (DEGs) were validated by real-time fluorescence quantitative polymerase chain reaction (qPCR) in another 12 drug-naïve patients with schizophrenia and 12 healthy controls. Results: We identified 542 DEGs, 51 DEGs, 732 DEGs, and 104 DEGs in PBMCs, dorsolateral prefrontal cortex (DLPFC), anterior cingulate gyrus (AnCg), and nucleus accumbent (nAcc), respectively. Five DEG clusters were recognized as having similar gene expression patterns in PBMCs and brain tissues by WGCNA. The pathway analysis illustrated these DEG clusters mainly enriched in several biological pathways, which related to phospholipid metabolism, ribosome signal transduction, and mitochondrial oxidative phosphorylation. The differential significance of PLAAT3, PLAAT4, PLD2, RPS29, RPL30, COX7C, COX7A2, NDUFAF2, and ATP5ME were confirmed by qPCR. Conclusions: This study found that the pathways associated with phospholipid metabolism, ribosome signal transduction, and energy metabolism have similar expression patterns in PBMCs and brain tissues of patients with schizophrenia. Our results supplied a novel insight for revealing the pathogenesis of schizophrenia and might offered a new approach to explore potential biological markers of peripheral blood in schizophrenia.